Metabolome and transcriptome analyses provide new insights into the mechanisms underlying the enhancement of medicinal component content in the roots of Acanthopanax senticosus (Rupr. et Maxim.) Harms through foliar application of zinc fertilizer - Sun, Tongze; Sun, Jialin; Liu, Yuli; Ren, Yanjun; Li, Yifeng; Shi, Chang; Nasr, Alyaa; Tang, Zhonghua; Abozeid, Ann (Frontiers in Genetics, 2023)
Acanthopanax senticosus (Rupr. et Maxim.) Harms is a perennial shrub of the Acanthopanax genus in the Araliaceae family and has a high medicinal value. The application of zinc fertilizer can improve the yield and quality of medicinal materials. However, there are limited reports on approaches to increase the content of medicinal components in A. senticosus, hindering the improvement of its medicinal quality. In this study, A. senticosus was treated with 0.1% (LZn) and 0.4% (HZn) zinc sprayed on the leaf surface. The effects of zinc treatment on the medicinal components in the roots of A. senticosus were analyzed by comprehensive metabolomics and transcriptomics analyses. A total of 316 metabolites were detected, with a prevailing occurrence of terpenoids and phenylpropanoids. We identified metabolites related to the medicinal components that were upregulated after Zn treatment, including 43 terpenoids, 19 phenylpropanoids, eight phenols, and three flavonoids. Combining differential gene expression and K-means analysis, we found 95, 65, and 25 upregulated genes related to phenylpropanoid biosynthesis, terpenoid biosynthesis, and flavonoid biosynthesis, respectively. Under different concentrations of Zn treatment, the upregulated metabolite biosynthesis-related genes and differentially expressed transcription factors varied. Pearson correlation network analysis revealed significant correlations among terpenoids, phenylpropanoids, flavonoids biosynthetic genes, and several transcription factors (ERFs, WRKYs, bHLHs, NACs, and MYBs). This study lays the foundation for understanding the metabolic processes in response to varying levels of zinc foliar spray and provides a theoretical basis for enhancing the efficiency of zinc fertilizer utilization in A. senticosus.